ANALISIS MINAT MAHASISWA DALAM MENGIKUTI KEGIATAN UKM RENANG UNIVERSITAS NEGERI SURABAYA (STUDI PADA MAHASISWA UNIVERSITAS NEGERI SURABAYA ANGKATAN 2011) - Fransinata, Arif; Marsudi, Imam (Jurnal Prestasi Olahraga, 2013)
The main target of swimming unit is not only as a maturity learning media in aunit, but also in coaching the students in UNESA. But, in recent years the number of member has decreased. The study aims to find out the interest and the factors which affect the students? interest in participating swimming students? activity unit UNESA.This research was qualitative descriptive approach that used two techniques sample (combination) which were purposive and SAS sample method towords 339 students from 5089 students in UNESA year 2011.The result of this research is that from 339 students of UNESA as many as 53.8% agreed with this swimming students? activity unit and 46.2% students do not agree. however, it is not suitable with the fact, which was more than 72.9% did not join in this swimming students? activity unit and 27.1% who joined. Number of students who did not attend this swimming students? activity unit, caused by some reasons, they are: spending a lot of energy 33.3%, wasting much time 27.2%, dangerous sport 20,6%, boring sport 13.6% and traumatic 5.3%. It can be concluded that swimming students? activity unit is still interested by students of UNESA although it has many difficulties to join it, such as it kind of sports which needs a lot of energy and wasting time.